Exploring Parental Aggression toward Teachers in a Public School Setting - David C. May; Jerry D. Johnson; Yanfen Chen; Lisa Wallace; Melissa Ricketts (Arizona State University, 2010)
Research regarding teacher experiences with school violence has focused almost exclusively on student perpetrators. Consequently, little is known about acts against teachers where parents are the primary aggressors. The present study attempts to fill that void by examining public school teachersâ experiences with problematic parental behavior. Using data from 5,971 P-12 teachers in one southeastern state, this study utilizes a descriptive and exploratory analytical framework and finds that teachers experience more verbal abuse than actual physical aggression, and that experiences vary according to teacher, school, and community characteristics. The article concludes with recommendations for policy/practice and for further research.